Evaluation of the Sexual Health Education of Teenage Males in a Middle School in Rural North Carolina - Dierolf, Karina (My University, 2015)
Teenage pregnancy has serious consequences for the young couple including limited education, inadequate employment opportunities, and adverse health outcomes (Alford & Houser, 2011). North Carolina is consistently among the nation’s leading states in teenage pregnancy and births. Teenage pregnancy has an enormous economic impact costing North Carolina taxpayers $325 million per year (The National Campaign to Prevent Teen and Unplanned Pregnancy, 2015). Although the most effective method of preventing pregnancy is to have both genders knowledgeable in contraceptive options and supportive of each other, pregnancy prevention and sexual health education has been disproportionately geared towards the female population (Starr, 2013). Adolescent males are receiving more education on the prevention of sexually transmitted infections than on pregnancy prevention, leading to gaps in their sexual health knowledge. This project was conducted at a middle school in rural eastern North Carolina. The middle school has a population of 524, represented by African American (44.2%), Hispanic (37.5%), and White (11.6%) students. The purpose was to evaluate the sexual health education provided to adolescent males in this rural school setting. The Healthy Youth Act of 2009 mandated comprehensive sexual health education for students in grades 7-9 in all North Carolina public schools. The project addressed two public health interventions: collaboration and policy development and enforcement. A senior nursing student collaborated with a school nurse, a family nurse practitioner, a health educator, and a physical/health education teacher to conduct this evaluation. The project objectives were to 1) obtain data on sexual health information received by adolescent males using a three-tiered algorithm, 2) interview 4 key informants on their role in sexual health education with males, and 3) observe sexual health education classes. The major finding of this program evaluation was the assessment form (RAAPS) used in the school-based health center may not have the types of questions that help identify sexual health needs of boys and the school nurse may have other knowledge that influences the referral action. Additionally, the school has a higher than expected number of at-risk students, with sixty percent of selected males with a completed RAAPS referred for further sexual health education. A written report of findings will be provided to the school administration and the school-based center advisory board.
Keywords: Sexual health; Health education; Teenage males